The Dynamics of Fiqh and Ushul Fiqh as a Treasury of Islamic Sharia for In-Depth Understanding - Jailani Jailani; Ahlam Sbaihat; Mahmoud Mohamed Hosny (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2023)
This research explores the dynamics of the discussions on Fiqh and Ushul Fiqh as the primary treasury within Islamic Sharia with the aim of obtaining in-depth understanding. The main focus of this research is to identify the roles and interactions between Fiqh and Ushul Fiqh in shaping a comprehensive understanding of Islam. The analytical method involves literature review and critical studies of classical texts as well as works by contemporary scholars. The research findings indicate that a profound understanding of Fiqh and Ushul Fiqh has a positive impact on strengthening the beliefs and religious practices of Muslims. The dynamics of these discussions encompass theological, legal, and methodological aspects that complement each other. The integration of Fiqh and Ushul Fiqh provides a robust framework for understanding and applying Islamic teachings in everyday life. This research contributes to the literature on in-depth understanding of Islam, emphasizing the importance of harmonizing Fiqh and Ushul Fiqh as the foundation for Muslims in living a religious life. The implications of these research findings can be used as a guide for researchers, practitioners, and Islamic thinkers in efforts to enhance a holistic understanding and practice of Islamic teachings